Human Fallibility and Sequential Decision-Making: Hierarchy Versus Polyarchy - Koh, Winston T. H. (Institutional Knowledge at Singapore Management University, 1992)
Decisions in organizations are often jointly made by individuals whose interests need not coincide. Even if they do, the quality of the decision depends crucially on the manner in which individual opinions are aggregated. This paper develops a model to analyse joint decision-making in large organizations under the key assumption that perfect information is impossible, so that human fallibility is present. The aim of the paper is to formalise some of the intuition associated with sequential decision-making in two stylised decision structures, namely: hierarchy and polyarchy. Incentive problems in the presence of human fallibility are also considered.